Evaluating the Role of Maqāṣid al-Sharīʿah in Formulating Ethical Frameworks for Artificial Intelligence in Islamic Jurisprudence - Wiwik Hidayati; Eka Pandu Cynthia (International Forum of Researchers and Lecturers, 2024)
The rapid advancements in Artificial Intelligence (AI) have raised significant ethical concerns across various sectors, necessitating the need for robust ethical frameworks to guide their development and implementation. This study explores the intersection of AI ethics and Islamic law, focusing on how Maqāṣid al-Sharīʿah, the higher objectives of Islamic law, can be applied to AI governance. By examining key Islamic principles such as justice, transparency, privacy, and human dignity, the study investigates how these values can provide a moral compass for addressing AI-related ethical challenges, such as algorithmic bias, privacy violations, and the erosion of human autonomy. The Maqāṣid al-Sharīʿah framework offers a proactive and vision-oriented approach, prioritizing societal well-being while ensuring the alignment of AI technologies with Islamic moral standards. Unlike traditional Islamic legal responses, which are often reactive and case-specific, the Maqāṣid approach promotes the anticipatory evaluation of technologies, emphasizing the need for a balance between technological innovation and ethical responsibility. The paper also discusses potential solutions to bridge the gaps between global AI ethics frameworks and Islamic ethical standards, including interdisciplinary collaboration and the development of hybrid regulatory models. Additionally, it highlights the need for continuous updates to Islamic legal frameworks to address emerging technological issues, ensuring that AI systems are ethically sound, Shariah-compliant, and beneficial to society. This study aims to contribute to the growing discourse on the ethical implications of AI from an Islamic perspective, offering insights into how Islamic law can play a crucial role in shaping the future of AI governance.